ANALISIS PENGARUH SIMPANAN, TINGKAT BAGI HASIL, DAN NON PERFORMING FINANCING (NPF) TERHADAP PEMBIAYAAN PADA PERBANKAN SYARIAH - Deni Pandu Nugraha; Sandra Karlina; Herni Ali (FE Program Studi Manajemen, 2019)
This research aims to determine Analyzed influence of Deposit, Level of Revenue Sharing, and Non Performing Financing (NPF) in Financing of Islamic Banks partially or simultaneously on Bank Syariah period 2011-2017. The population in this study is the Islamic Bank operating in Indonesia for 5 years. This study using purposive sampling method with variable simpanan, bagi hasil, and NPF at the Financing. After being selected, the target population amounted 7 banks, among which the Syariah Mandiri, Muamalat, BRI Syariah, BNI Syariah, BCA Syariah, BJB Syariah and Mega Syariah. Based on the test F, note that in this study the variabel Deposit (DPK), Level of Revenue Sharing, and NPF have affect the results simultaneously to Islamic Banks. Adjust R2 in this study indicate that all independent variables contributed as much as 59% on the dependent variable. While 41% are influenced by the effect of other independent variables which are not described in this model Key words: Deposit (DPK), Level of Revenue Sharing, Non Performing Financing, and Islamic Banks